Cityscapes of Violence in Karachi : Publics and Counterpublics - Edited by Nichola Khan (Karachi Oxford University Press, 2017)
This work enlists some controversies that understanding, writing about and publishing on violence in Karachi entails. It brings into conversation some prominent academics - including anthropologists and political scientists - journalists, writers and activists
Include Illustrations,Bibliography and Index
Keywords: Karachi (Pakistan) Politics and Government. -- Political Violence -- History Asia India and South Asia